The Influence of Location, Price and Promotion on Decisions to use Shipping Services AT SPX Express Pematangsiantar - Sitanggang, Augustinus S; Simanjuntak, Dean; Faisal , Ahmad; Sihombing, Maruli; Rajagukguk, Enjel Jaya; Panjaitan , Santi Rohdearni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The results of this study are to analyze the influence of location, price and promotion on the decision to use shipping services at SPX Express. The number of samples in this study was 60 respondents and used the random sampling method. This study uses the multiple linear regression test analysis method. The results of this study indicate that there is a simultaneous influence on the variables (location, price and promotion) on the decision to use shipping services, the significant value is below 0.05 and the Fcount value (39.898)> Ftable (2.77). The results of this study also show that the t-value on the location variable is (2.641), the price is (2.127) and the promotion is (2.753) greater than the t-table (2.00) so it is stated that there is an influence on the decision of the delivery service. In the determination test, there is an influence of 66.5% of the independent variables (location, price and promotion) on the dependent variable (decision of the delivery service). Meanwhile, 33.6% is influenced by other variables and is not included in this regression analysis, such as brand image, brand equity, product quality and others.